Positive effect of learning foreign language in a healthy elderly - Ahmad Muhammad Diponegoro (Journal on English as a Foreign Language, 2012)
The study of elderly found that almost all cognitive functions decline with age. Results of previous studies have shown that cognitive training related to everyday life (reading aloud and learning vocabularies and wisdom), namely learning intervention or therapy, can improve two cognitive function (executive functions and processing speed) in elderly people. This study investigates the positive effects of learning foreign language on cognitive functions of an elderly person. This study provides sufficient evidence of learning foreign language effectiveness in a healthy elderly.  Method used is  one single case subject design. A healthy elderly was asked to read aloud and memorize several Quran chapters and verses and write Arabic verbs proposition and several nouns found it the memorized verses and put it into correct sentences. The written words are concerning daily life activity. Since the Qur’an has best structure of Arab sentence, memorizing it help to understand the Arabic sentences properly. The finding support the previous research that the elderly able to improve their cognitive processes and ability through studying foreign language.